Studi Pendahuluan terhadap Hasil Belajar Siswa Sekolah Dasar Sebelum Implementasi LKPD IPAS Berbasis Discovery Learning - Sari, Emilia; Aryandi, Andi; Pramudiyanti; Pramita Sylvia Dewi (STKIP PGRI Bandar Lampung, 2024)
Primary education plays an important role in shaping the foundation of students' knowledge, especially in Natural and Social Sciences (NSP) subjects in grade 4. Choosing grade 4 as the focus of learning is very strategic because at this age, children are in a critical stage of cognitive development where they begin to be able to think logically and understand more abstract concepts. LKPD is a learning tool designed to provide guidance and steps to students in the form of worksheets that contain instructions, steps, and tasks to be completed. LKPD serves as a medium that helps students organize and internalize learning material more effectively, as well as develop analytical thinking skills and problem solving through hands-on and exploratory activities. The photosynthesis material in the 4th grade Natural and Social Sciences (IPAS) subject of the Merdeka Curriculum was chosen for research because photosynthesis is a basic concept that is very important for students' understanding of the plant life cycle and the basics of ecosystems. Photosynthesis teaches students about how plants produce food and oxygen, which are essential for the life of all living things. A solid understanding of the photosynthesis process can help students appreciate the importance of protecting the environment and increase their awareness of environmental issues. In addition, it lays the foundation for more complex science lessons later in their education. Conventional learning methods are often unable to optimally motivate students, resulting in low learning outcomes. To overcome this problem, the development of Discovery Learning-based Learner Worksheets (LKPD) is an alternative solution. This study aims to determine the initial picture of student learning outcomes using LKPD. The method used is descriptive research. Data collection was carried out using a test instrument. The results of the study were an average of 55. This result shows that the average value of students does not yet have a basic understanding of the concept of photosynthesis. The follow-up of the results of this study is the need to develop Discovery Learning-based LKPD.